The Relationship Between Energy Commodity Prices and Electricity and Market Index Performances: Evidence from an Emerging Market. Issue 9 (1st September 2016) - Ordu, Beyza Mina; Soytaş, Uğur
ABSTRACT: We investigate the effect of energy commodity price movements on market and electricity index returns in Turkey for the periods before, during, and after the year 2008. Although the Turkish economy is highly reliant on oil, we find that oil price does not lead either electricity or market indexes. This might be attributable to sluggish integration of financial markets in Turkey compared to developed markets. Natural gas price leads electricity index in the pre-2008 period. Its significance is reduced following the decline in natural gas usage in electricity production. This suggests that commodity dependence may be driving the link between commodity and asset prices in related sectors.